2021
DOI: 10.1016/j.heliyon.2021.e07849
|View full text |Cite
|
Sign up to set email alerts
|

Alkaloidal extract from Carica papaya seeds ameliorates CCl4-induced hepatocellular carcinoma in rats

Abstract: Background Hepatocellular carcinoma (HCC) is the third cause of cancer-related mortality globally. However, available treatments are expensive and are associated with adverse effects or poor treatment outcomes in advanced disease. Meanwhile, plants like Carica papaya have demonstrated various biological activities that further studies may lead to the identification of newer and safer treatment options for HCC. Aim To evaluate the anticancer ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Based on several studies showed that papaya seed extract is effective in preventing skin inflammation caused by bacteria and parasite growth, and together with other ingredients such as chitosan may provide a better effect as an antibacterial compound (Gnanamangai et al 2022). Alkaloid extracts from papaya seeds can be used as therapeutic agents for hepatocellular carcinoma by the mechanism of increasing the histoarchitecture of liver tissue (Barffour et al 2021). The other property which is widely studied of papaya seeds is anti-cancer activity.…”
Section: Introductionmentioning
confidence: 99%
“…Based on several studies showed that papaya seed extract is effective in preventing skin inflammation caused by bacteria and parasite growth, and together with other ingredients such as chitosan may provide a better effect as an antibacterial compound (Gnanamangai et al 2022). Alkaloid extracts from papaya seeds can be used as therapeutic agents for hepatocellular carcinoma by the mechanism of increasing the histoarchitecture of liver tissue (Barffour et al 2021). The other property which is widely studied of papaya seeds is anti-cancer activity.…”
Section: Introductionmentioning
confidence: 99%